Microstructural Changes Induced by CO2 Exposure in Alkali-Activated Slag/Metakaolin Pastes - Bernal, Susan A. (Frontiers in Materials, 2016)
The structural changes induced by accelerated carbonation in alkali-activated slag/ metakaolin (MK) cements were determined. The specimens were carbonated for 540 h in an environmental chamber with a CO2 concentration of 1.0 ± 0.2%, a temperature of 20 ± 2ºC, and relative humidity of 65 ± 5 %. Accelerated carbonation led to decalcification of the main binding phase of these cements, which is an aluminium substituted calcium silicate hydrate (C-(N-)A-S-H) type gel, and the consequent formation of calcium carbonate. The sodium-rich carbonates trona (Na2CO3·NaHCO3·2H2O) and gaylussite (Na2Ca(CO3)2·5H2O) were identified in cements containing up to 10 wt.% MK as carbonation products. The formation of these carbonates is mainly associated with the chemical reaction between the CO2 and the free alkalis present in the pore solution. The structure of the carbonated cements is dominated by an aluminosilicate hydrate (N-A-S-H) type gel, independent of the MK content. The N-A-S-H type gels identified are likely to be derived both from the activation reaction of the MK, forming a low-calcium gel product which does not seem to undergo structural changes upon CO2 exposure, and the decalcification of C-(N-)A-S-H type gel. The carbonated pastes present a highly porous microstructure, more notable as the content of MK content in the cement increases, which might have a negative impact on the durability of these materials in service.